PARTISIPASI MASYARAKAT DALAM MUSYAWARAH PERENCANAAN PEMBANGUNAN DI KELURAHAN SILAE KECAMATAN ULUJADI KOTA PALU - Haryadi, Ahmad (Katalogis, 2016)
The problem behind this research was that the community had less participation in the discussion for development Planning in Kelurahan Silae. This resulted in not achieving the main purpose of this program. This research aimed at investigating the participation, attitudes and views of the villagers in the discussion for village development planning in Kelurahan Silae, the sub-district of Ulujadi, the City of Palu. The research used C. Ericcson’s Participation Theory (Slamet, 1993:89) in wich participation is divided into three roles: planning, implementation, and control. This research used qualitative method and employed purposive sampling technique with five employed. The methods used for collection data wereobservation, interview, and documentation. It is found that community participation in the discussion for development planning in Kelurahan Silae, the Sub-district of Ulujadi, the City of Palu did not run well. The villager’s attitudes and view reflection the three roles under investigation were they apathies, did not care, and did not put trust in the local government. These problem came us because the voices of the community were not responded well by local government’s parties. The relevant parties provided less extension and information relating to the mechanism, from the initial stage to the implementation of the village community discussion and to the fundable program within the local government of Palu.